UNVEILING THE POLITICAL SYMPHONY OF CELEBRITY ENDORSEMENTS IN SOUTH ASIA’S TAPESTRY, WITH A SPOTLIGHT ON PAKISTAN’S DYNAMIC VOTING INTENTIONS FOR POLITICAL LEADERS - Moneeba Iftikhar; Samaan Kashif; Dr. Sapna MumtaZ; Mgr. et Mgr. Ondřej Podeszwa (International Journal of Contemporary Issues in Social Sciences, 2024)
In the realm of political science and communication studies, the profound influence of celebrity endorsements on politics often goes unrecognized. This study addresses this gap by investigating the intricate dynamics of celebrity endorsements and their effect on the voting preferences of young voters in Pakistan, with a specific focus on both pre-and post-2018 elections. Through a meticulous exploration of mediating factors, we analyze the attitudes and voting inclinations of 501 participants, shedding light on the significant impacts witnessed in the evolving political landscape leading up to the 2024 elections. Our findings not only contribute to the existing political advertising literature but also pave the way for future research initiatives. The study concludes with comprehensive insights, recommendations, and theoretical implications, providing a nuanced understanding of the role of celebrity endorsements in shaping political landscapes during this critical period.